Suppression of Partial Discharge in Package Insulation Under Square-Wave Voltage by Plasma-Enhanced Film Deposition - Guan, Xiuhan; Zhang, Fengjie; Xu, Junhao; Cheng, Hongtu; Wang, Yalin; Zhu, Xi; Fang, Zhi (International Conference on Electrical Materials and Power Equipment (Online), 2025)
The rapid development of power modules, characterized by high d v / \text{dt} switching, subjects package insulation to severe electrical stress under square-wave voltage, leading to detrimental partial discharges (PD) at triple point (TP) region. This study introduces a precision atmospheric pressure micro-plasma jet ( μ -APPJ) technique using HMDSO precursor to deposit Si-containing dielectric film at metal/insulation interface. By optimizing HMDSO volume fraction ( φ_{\text {HMDso }} ), the effect of plasma treatment conditions on PD suppression at 5 \text{kHz} / 50 % duty-cycle square-wave voltage is evaluated. The results show that Ar/HMDSO plasma-deposited films are effective in suppressing the PD intensity, but introduce an unanticipated PD phenomenon at the high-level stage. With the increase of HMDSO volume fraction, the maximum PD amplitude of the unpotted sample at φ_{\text {HMDSO }}=0.24 % decreased to 12.25 mV (84.6 % reduction) and the PD is completely suppressed in the high-level stage. The number of PDs of the potted sample is reduced by 56.1 %, with an average amplitude reduction of 53.9 %, and the breakdown voltage is increased to 17 kV. This technique provides a novel approach to improve the insulation reliability of power modules.